COVID-19’s impact on neglected pharmaceutical staff: wake-up call for needed research - Richard Antony Powell (BMC, 2021)
Abstract Discussion of the necessity of the compulsory vaccination of UK patient-facing care workers as an employment conditionality has deflected from the initial and ongoing impact of Coronavirus disease on relatively neglected occupational groups themselves, including community pharmacists. This commentary highlights the relative lack of research investigating the mental health and wellbeing impact of the pandemic on this occupational group in England and urges further study of their needs and experiences to inform evidence-based supportive psychological interventions.